Analisis Kemampuan Adaptasi Dan Motivasi Terhadap Kinerja Karyawan Di Universitas PGRI Semarang - Sutrisno Sutrisno; Bayu Kurniawan (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2020)
This study aims to analyze the extent to which the ability to adapt and motivate employee performance at the PGRI University Semarang so that later the results obtained can be used as input for the university to be able to conduct future restructuring. This study took a sample sample of the entire population of 123 employees. The data analysis method used is quantitative analysis using data quality test, classical assumption test, t statistical test, F statistical test, multiple linear regression analysis test, and the coefficient of determination. The results of the study indicate that environmental variables have an influence on performance. motivation has no effect on employee performance.